Addressing health inequalities in diverse, rural communities: An unmet need - Laura Richman; Jay Pearson; Cherry Beasley; John Stanifer (Elsevier, 2019)
Research on rural health needs to represent the diverse demographics of these regions by carefully considering the distinct characteristics, inequities, and stressors occurring in rural communities. Drawing from our own findings and other empirical investigations examining diverse rural communities, we propose several considerations to guide future endeavors toward more inclusive rural health research. These include population-health assessment tools that consider minority stress and intervention strategies designed to reflect both the environmental and socio-cultural contexts of rural residents.